Keberfungsian Desain Penanda Identitas Berhuruf Cina pada Restoran dan Cafe Di Bandung - Elizabeth Susanti Gunawan; Naomi Haswanto; Dody Achmad (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2011)
After the revocation of prohibition of Chinese language usage in 2000 by President Abdurrahman Wahid, corporate's identity signs using Chinese letters are flourishing Indonesia. The appearances of identity sign using Chinese letters in the last 10 years is quite confusing considering not many people can read them. The function of identity signs to convey information for public are not fully achieved. Study about how the usage of Chinese letter as a foreign language in identity sign in Bandung with low level of interpretation but can create strong image with high rate of effectiveness and also about the philosophy of Chinese culture contained in the elements that formed identity sign such as name selection, logo shape, Chinese typography, and color, has not been written.This study assess the existence of restaurant's/cafe's identity sign located in Bandung, West Java. By analyzing the elements in Chinese letter identity sign, this study seeks to evaluate the legibility of Chinese letter identity signs. Knowing the exact level of effectiveness of a identity sign for the next design, designers can notice more the recipient background, so they can still functioning as identity sign and convey information about the existence of restaurants and cafes. In addition, this study tries to identify the elements of Chinese culture contained in the Chinese letter identity sign, by elaborating visual element analysis of identity signs, such as: the selection of names, colors, shapes, the usage of symbols in Chinese culture and font type. Chinese society is a society that its culture has evolved over thousands of years. Starting from the color in Chinese culture has its own significance, also typical objects in Chinese culture has profound meaning for the people. Some elements of Chinese culture can be felt so deeply in restaurant/cafe identity sign that is designed in Chinese letter.Chinese letter that serves as text to convey information becomes ineffective, because of its presence in Bandung, a city that the majority of communities can not speak Chinese. Therefore, Chinese characters used in identity signs in Bandung shift their function from text (logotype) to be ornaments (logogram) that give the feel and identity of Chinese. So text message is no longer the main thing to be said, but image is, as a primary goal to be conveyed.